1996
DOI: 10.1007/bf00208313
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the role of the Arabidopsis gene MONOPTEROS in vascular development and plant cell axialization

Abstract: In the embryo of Arabidopsis thaliana (L.) Heynh., formation of the hypocotyl/root axis is initiated at the early-globular stage, recognizable as oriented expansion of formerly isodiametric cells. The process depends on the activity of the gene MONOPTEROS (MP); mp mutant embryos fail to produce hypocotyl and radicle. We have analyzed the morphology and anatomy of mp mutant plants throughout the Arabidopsis life cycle. Mutants form largely normal rosettes and root systems, but inflorescences either fail to form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
332
0
4

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 439 publications
(353 citation statements)
references
References 10 publications
17
332
0
4
Order By: Relevance
“…Recently, several genetic and physiological studies strongly suggested that auxin transport and auxin response are required for normal embryogenesis (Przemeck et al, 1996;Hadfi et al, 1998;Hamann et al, 1999; Chen et al, 2001). Our studies show that AXR1 and ECR1 are expressed during embryo development, despite the fact that axr1 embryos do not have an obvious defect.…”
Section: Function Of Axr1-ecr1 During Embryogenesismentioning
confidence: 99%
“…Recently, several genetic and physiological studies strongly suggested that auxin transport and auxin response are required for normal embryogenesis (Przemeck et al, 1996;Hadfi et al, 1998;Hamann et al, 1999; Chen et al, 2001). Our studies show that AXR1 and ECR1 are expressed during embryo development, despite the fact that axr1 embryos do not have an obvious defect.…”
Section: Function Of Axr1-ecr1 During Embryogenesismentioning
confidence: 99%
“…Because it is known that auxin plays an essential role in the patterning of vascular tissues (Przemeck et al, 1996;Hardtke and Berleth, 1998), possible alterations to auxin-cytokinin interactions in the pls mutant, which are attributable to increased cytokinin levels or sensitivity or reduced auxin levels or sensitivity, could account for the observed reduced vascularization in the pls leaf.…”
Section: Pls Functionmentioning
confidence: 99%
“…Appropriate distribution of auxin has been shown to be necessary for a number of developmental processes. Normal embryogenesis, for example, requires auxin transport (Cooke et al, 1993), and the Arabidopsis mutants lop1, pin1-1, and monopterous (Okada et al, 1991;Carland and McHale, 1996;Przemeck et al, 1996), which may be altered in auxin transport, have altered vascular, floral, and pattern development, respectively.…”
mentioning
confidence: 99%